Modification of the levels of delta-aminolevulinic acid dehydratase in chronic alcoholic patients - Wider, E.A. (1997)
Medical and biochemical analysis were performed on 58 patients with chronic alcoholism. In accordance with medical characterisation, patients were divided in three groups: A (patients having only hepatopathy), B (patients with hepatopathy and neuropathy) and C (patients having only alcoholic neuropathy). Simultaneously, several parameters related to heme biosynthesis were examined. Urinary delta-aminolevulic acid (ALA), porphobilinogen (PBG) and porphyrins and fecal porphyrins measurements did not show significant difference among all studied groups. The activities of ALA-dehydratase (ALA-D), uroporphyrinogen-I-synthase (URO-I-S) and uroporphyrinogen-III-synthase (URO-III-S) were monitored in peripheral erythrocytes. From the enzymes measured, only ALA-D levels in groups B and C were significantly depressed (p < 0.002) compared with normal subjects. The decrease in ALA-D correlated with the degree of neuropathy.